2011
DOI: 10.3201/eid1705.101654
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Oral Transmission of Atypical Scrapie to Sheep

Abstract: Such transmission results in peripheral tissue infectivity that is not detectable by current surveillance screening methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 37 publications
4
59
2
Order By: Relevance
“…Data from an oral challenge study in sheep also indicate that very early exposure (within 24 hours of birth) can lead to transmission of the disease, resulting in clinically affected animals displaying a similar clinic-pathological pattern to those observed in natural cases (Simmons et al, 2010). It is probably too early, therefore, to conclude if this is a spontaneous, non-contagious disorder or if it can behave like other TSE agents circulating in small ruminants.…”
Section: Exposure and Transmissionmentioning
confidence: 93%
See 1 more Smart Citation
“…Data from an oral challenge study in sheep also indicate that very early exposure (within 24 hours of birth) can lead to transmission of the disease, resulting in clinically affected animals displaying a similar clinic-pathological pattern to those observed in natural cases (Simmons et al, 2010). It is probably too early, therefore, to conclude if this is a spontaneous, non-contagious disorder or if it can behave like other TSE agents circulating in small ruminants.…”
Section: Exposure and Transmissionmentioning
confidence: 93%
“…While the contagiousness of AS under natural conditions is still debated, the transmissibility of the AS agent by the intracerebral route is clearly established in both rodent models (transgenic animals overexpressing the ovine PrP gene (Le Dur et al, 2005)) and in sheep (Simmons et al, 2007;Simmons et al, 2010). Data from an oral challenge study in sheep also indicate that very early exposure (within 24 hours of birth) can lead to transmission of the disease, resulting in clinically affected animals displaying a similar clinic-pathological pattern to those observed in natural cases (Simmons et al, 2010).…”
Section: Exposure and Transmissionmentioning
confidence: 99%
“…Nevertheless, oral transmission of atypical scrapie has been recently achieved in AHQ/AHQ sheep (10). In that study, although no detectable PrP Sc was found outside the brain during the preclinical and the clinical stages of the disease, prion infectivity was found in the distal ileum.…”
mentioning
confidence: 97%
“…This simple modification has increased significantly the sensitivity of detection of atypical scrapie during surveillance schemes. Unlike classical scrapie, in atypical scrapie the agent is not distributed in peripheral tissues systematically which, in conjunction with its limited distribution in the obex and widespread distribution in the cerebral and cerebellar cortex, have led to the belief that this TSE occurs sporadically 70,71) . This is supported by epidemiological data indicating that it is not infectious under natural conditions 72) , although it can be transmitted experimentally via the oral route 71) .…”
Section: Atypical Scrapiementioning
confidence: 99%